Progettualità utopica e identità lavorative - Immacolata Messuri (Firenze University Press, 2017)
The text deals with the theme of professional skills from the point of view of training and counseling, and the utopia topic as the commitment to protect to the rules im-posed by political and economic crises. Evidence shows the importance of projects like process by which we recognise ourselves in the direction of well-being.